What are solids, liquids, and gases?: exploring science with hands-on activities - Spilsbury, Richard; Spilsbury, Louise (Enslow Elementary Berkeley Heights, NJ, 2008)
"A beginners look at the states of matter for third and fourth grades"--Provided by publisher